Biosynthesis of α MnO2 nanorods using Coleus amboinicus leaf extract and its adsorption performance of Pb(II) from aqueous solutions. - Rejani Padmavathiamma; Rani Pillai (Journal of Water and Environmental Nanotechnology)
Heavy metals are known to be toxic for living organisms even if they are present at low levels. Water pollution by heavy metals from industries is a dangerous environmental problem. Due to the ease, flexibility, and cost-effectiveness of the remediation process, adsorption has been widely implemented in heavy metal wastewater treatment. In the present study, nanostructured manganese oxide was used for the removal of the heavy metal ions from aqueous solutions by a batch adsorption method and have been modelled using classical Langmuir and Freundlich adsorption isotherms. we have successfully synthesized an efficient adsorbent through a cost-effective and eco-friendly method. Bio synthesis is widely applied for the synthesis of nano materials . Various techniques such as XRD, FTIR, SEM EDX ,TEM and UV–VIS spectroscopy have been used to characterize the nanometal oxide. The obtained nano manganese oxide rods have very good adsorption efficiency due to the presence of some functionalities associated with the oxide material.